(untitled) - Price, Kingsley (Boston, 1962)
Education is a subject which now commands a great deal of attention. Because of this manner of defining "philosophy of education" several of the theries presented in this volume must be regarded as some what incomplete and implicit philosophies of the subject.
Keywords: Giáo dục,Education; Triết học,Lịch sử,Philosophy,History